Entrepreneurial Failue: A Cognitive and Emotional Perspective of Learning - Anca, Cristiana (2007)
Vision, opportunity, strategy, risk, responsibilities, fear, challenge, innovation, high flyers, success, failure, change, confidence, learning - entrepreneurship represents a difficult undertaking in which these factors form the world of the people that dare venture. Substantially different than other areas of business, entrepreneurship serves both individual goals of achievement and performance, as well as wider societal goals, such as developing new markets, mobilizing capital resources, introducing new technologies and products through innovation, and creating employment. Due to the high degree of novelty and uncertainty in which entrepreneurs act, as well as to the difficulties of starting a business, many new ventures fail in the start-up period. A loosely constructed term, 'failure' is equivalent to a variety of concepts such as bankruptcy, involuntary liquidation, financial distress, insolvency, etc. and is defined for the purpose of this paper as 'the termination of an initiative that has fallen short of its goals'. (McGrath, 1999, page 14)